Determinant Factor Analysis of Traveler Loyalty by Push and Pull Motivation - Rivaldi Arissaputra; Sarah Sentika (Budapest International Research and Critics University, 2022)
As a network of creative cities by the United Nations Educational, Scientific and Cultural Organization (UNESCO), Bandung announced that the city of Bandung was listed as one of the innovative city networks of the UNESCO Creative Cities Network, which is very attractive for tourists. In general, tourists are divided into different segments. Geographical segmentation in terms of area is the most prominent thing among tourists, especially in this study. The research subjects were tourists from the Greater Jakarta area who had visited Bandung several times. The sample used in this study was 100 people, conducted using a questionnaire and processed by descriptive-verificative analysis techniques. This study aims to explain the determinants of tourist loyalty to the city of Bandung by measuring the influence of the driving motivation and pull motivation variables on tourist loyalty. The results showed that the driving motivation did not affect the loyalty of Jabodetabek tourists, while the pull motivation affected the loyalty of Jabodetabek tourists.